Evaluation of motor disorders in children who were born prematurely, according to the standard electroencephalography - О. O. Riga; І. V. Gordiienko (Zaporožskij Medicinskij Žurnal)
Aim. To determine the diagnostic value of the standard EEG patterns in disorders of motor development of born prematurely young children using logistic regression analysis.